2022
DOI: 10.1111/ppa.13529
|View full text |Cite
|
Sign up to set email alerts
|

Fungi as potential factors limiting natural regeneration of pedunculate oak (Quercus robur) in mixed‐species forest stands in Poland

Abstract: Dieback of young Quercus robur seedlings can limit natural regeneration in mixed‐species forest stands in Poland. The aim of this study was to examine the role of fungi in the dieback of oak seedlings in central Europe. Fungi were isolated from the stems and roots of Q. robur, from both healthy seedlings and seedlings with symptoms, that were sampled from four stands in Poland. In total, 111 distinct taxa were identified. Ascomycota was dominant, representing 95.6% of the isolates. Among the taxa identified, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
(61 reference statements)
1
11
0
1
Order By: Relevance
“…Climate change scenarios, particularly more severe droughts, will contribute to the greater future mortality of pedunculate oak trees [1]. Successful natural regeneration in oak forests depends on site fertility, soil moisture, overstory density, light availability, root competition from the parent trees, fungal diseases and, predominantly, seed production [2,3]. The interannual cycles of seed production in pedunculate oak range from 3 to Metabolites 2022, 12, 756 2 of 21 8 years [4] and are further disturbed by temperature differentials between consecutive years [5].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change scenarios, particularly more severe droughts, will contribute to the greater future mortality of pedunculate oak trees [1]. Successful natural regeneration in oak forests depends on site fertility, soil moisture, overstory density, light availability, root competition from the parent trees, fungal diseases and, predominantly, seed production [2,3]. The interannual cycles of seed production in pedunculate oak range from 3 to Metabolites 2022, 12, 756 2 of 21 8 years [4] and are further disturbed by temperature differentials between consecutive years [5].…”
Section: Introductionmentioning
confidence: 99%
“…paeoniae on mistletoe. As with oak seedlings (Jankowiak et al, 2022), F . paeoniae was isolated from healthy leaves of V .…”
Section: Discussionmentioning
confidence: 99%
“…and Populus sp. in China (Wang et al, 2022) as well as Quercus robur L. (Jankowiak et al, 2022), Fagus sylvatica L. (Stępniewska et al, 2021) and Populus tremula L. (Jankowiak, unpublished data) in Poland. Therefore, we suspect that F .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Jankowiak, Bilański, et al (2016) demonstrated that naturally regenerating silver fir seedlings can be infected by Gyoerffyella species, leading to seedling decline. In addition, fungal infection has been linked to the negative health of pendunculate oak seedling in mixed‐species forest stands in Poland (Jankowiak et al, 2022).…”
Section: Introductionmentioning
confidence: 99%